ANTESEDEN KEPUASAN DAN RASA PERCAYA SERTA KONSEKUENSINYA TERHADAP INTENSI PERILAKU - Wenny Chandra Mandagie (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
The purpose of this study to analyze the factors affecting the intentions of alumni who are willing to assist their university, whether financial or non-financial. The intentions of alumni are consequences of satisfaction and trust, where satisfaction and trust are the mediating variables of academic experience, current income, relation and agency image. The study was conducted through a survey method that included 250 respondents living in Jakarta, with middle and upper class economic levels. The sampling technique used is proportionate stratified random sampling. Structural Equation Modeling (SEM) was used to analyze the data. The finding from this study is the antecedent factors of satisfaction and trust including academic experience, income, relationships, and institution image that are proven to be positive and significantly influential in satisfaction and trust, partially or simultaneously. The behavior intention as a consequence of trust and satisfaction are found to be positive and significant although only moderate. Based on the findings, Indonesian higher education has to improve student’s satisfaction and trust through improvement of academic experience, relationship and institution image because the alumni will measure their satisfaction based on their current income. Therefore, for further research it is advisable to explore motivational factor, family education values and cultural factors as antecedents of behavior intention.